Bone marrow‐derived mesenchymal stem cells inhibit CD8+ T cell immune responses via PD‐1/PD‐L1 pathway in multiple myeloma. (7th May 2021) - Liu, Z.; Mi, F.; Han, M.; Tian, M.; Deng, L.; Meng, N.; Luo, J.; Fu, R.
Summary: High expression of the inhibitory receptor programmed cell death ligand 1 (PD‐L1) on tumor cells and tumor stromal cells have been found to play a key role in tumor immune evasion in several human malignancies. However, the expression of PD‐L1 on bone marrow mesenchymal stem cells (BMSCs) and whether the programmed cell death 1 (PD‐1)/PD‐L1 signal pathway is involved in the BMSCs versus T cell immune response in multiple myeloma (MM) remains poorly defined. In this study, we explored the expression of PD‐L1 on BMSCs from newly diagnosed MM (NDMM) patients and the role of PD‐1/PD‐L1 pathway in BMSC‐mediated regulation of CD8 + T cells. The data showed that the expression of PD‐L1 on BMSCs in NDMM patients was significantly increased compared to that in normal controls (NC) (18·81 ± 1·61 versus 2·78± 0·70%; P  < 0·001). Furthermore, the PD‐1 expression on CD8 + T cells with NDMM patients was significantly higher than that in normal controls (43·22 ± 2·98 versus 20·71 ± 1·08%; P  < 0·001). However, there was no significant difference in PD‐1 expression of CD4 + T cells and natural killer (NK) cells between the NDMM and NC groups. Additionally, the co‐culture assays revealed that BMSCs significantly suppressed CD8 + T cell function. However, the PD‐L1 inhibitor effectively reversed BMSC‐mediated suppression in CD8 + T cells. We also found that the combination of PD‐L1 inhibitor and pomalidomide can further enhance the killing effect of CD8 + T cells on MM cells. In summary, our findings demonstrated that BMSCs in patients with MM may induce apoptosis of CD8 + T cells through the PD‐1/PD‐L1 axis and inhibit the release of perforin and granzyme B from CD8 + T cells to promote the immune escape of MM. Abstract : (A‐B)The morphology of BMSCs subsequent to being passaged for 72 h of normal controls and NDMM patients. (P3, ×40; Scale bar: 100 um). The cell surface markers (C) CD34, (D) CD45, (E) CD73, (F) CD90, and (G) CD105 of BMSCs were detected by FCM.